Effectiveness of N‐Acetylcysteine for the Prevention of Contrast‐Induced Nephropathy: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 9 (23rd September 2016) - Xu, Renfan; Tao, Anyu; Bai, Yang; Deng, Youbin; Chen, Guangzhi
Abstract : Background: Conflicting results have been obtained in trials that have evaluated the prophylactic efficacy of N ‐acetylcysteine (NAC) pretreatment in the prevention of contrast‐induced nephropathy (CIN). In this meta‐analysis of randomized controlled trials, we aimed to assess the effectiveness of NAC treatment for the prevention of CIN. Methods and Results: PubMed, EMBASE, and the Cochrane Library were electronically searched from inception to January 2016 for all relevant studies. The weighted relative risk (RR) and corresponding 95% CI for incident CIN were estimated using random effects models. Standard methods for assessing statistical heterogeneity and publication bias were used. The study included 11 480 participants and 1653 cases of CIN. The incidence of CIN was 12.8% in the NAC group versus 16.0% in the control group (RR: 0.76, 95% CI: 0.66–0.88, P =0.0002). In the patients undergoing coronary angiography, the incidence of CIN in the NAC group versus the control group was 13.7% versus 17.2% (RR: 0.74, 95% CI: 0.63–0.87, P =0.0002); in those undergoing peripheral angiography, the incidence was 6.4% versus 5.8% (RR: 1.00, 95% CI: 0.42–2.40, P =1.00); in those undergoing computed tomography, the incidence was 7.7% versus 14.8% (RR: 0.51, 95% CI: 0.29–0.89, P =0.02). Conclusions: Our meta‐analysis showed an inverse and significant association between NAC supplementation and risk of CIN in patients undergoing coronary angiography and computed tomography, while a protective role for NAC in patients undergoing peripheral angiography was not obvious.